Assessment of the Yalova University Engineering Faculty Building using the B.E.S.T. green building certification system - Ozan Efe; Rabia Özdemir; Sena Işik; İlayda Durmuş; Ümit Ünver (International Journal of Sustainable Energy, 2022)
Currently, there is no official green or sustainable built environment evaluation system in Turkey. When a certification is required for a building or a site, various certification systems are employed. To meet the demand, the Turkish Green Building Council released an evaluation system called B.E.S.T. in 2013. In this paper, the B.E.S.T. evaluation system is introduced as well as a sample application. The evaluation of the Yalova University Engineering Faculty Building using the B.E.S.T. evaluation system is presented. Field research was conducted and evidentiary documents were gathered in preparation. The study employed both analytical and field research methodologies in this regard. As a result of the study, Yalova University Engineering Faculty Building was assessed to be eligible for the lowest level certificate, the ‘Approved’ degree of the B.E.S.T. evaluation system. Furthermore, the results achieved with the B.E.S.T. were compared to those acquired previously with other green or sustainable building evaluation systems. HIGHLIGHTS - An exemplary set of the evaluation was performed for university campus buildings with the B.E.S.T. certification system. - The conducted case study is one of the earliest samples of B.E.S.T. evaluations. - A comparison of B.E.S.T. with LEED and BREAM is provided. - The importance of establishing a local certification system has been discussed.